2022
DOI: 10.1021/acsomega.2c05794
|View full text |Cite
|
Sign up to set email alerts
|

Protein C-Terminal Tyrosine Conjugation via Recyclable Immobilized BmTYR

Abstract: Protein modification plays an essential role in biological and pharmaceutical research. Due to the ordinary selectivity and inevitable damage to proteins of chemical synthetic methods, increased efforts were focused on biocatalysts which exhibited high regioselectivity and mild reaction conditions. However, separation of the biocatalysts and modified proteins remained a problem, especially when scaling up. Here, we developed a simple method for site-specific protein modification with a recyclable biocatalyst. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…A heterogeneous system comprising tyrosinase immobilized on magnetic beads was lately reported by Ji et al to ease the purification of protein conjugates post oxidation with the enzyme. 127 The enzyme bound to a solid phase could be readily removed from the reaction mixture by a magnetic device and was recyclable after a washing cycle with buffers. The authors then demonstrated the applicability of this reaction system in a robust peptide and protein conjugation process with aniline derivatives.…”
Section: Selective Functionalization and Conjugation At Tyr Residues ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A heterogeneous system comprising tyrosinase immobilized on magnetic beads was lately reported by Ji et al to ease the purification of protein conjugates post oxidation with the enzyme. 127 The enzyme bound to a solid phase could be readily removed from the reaction mixture by a magnetic device and was recyclable after a washing cycle with buffers. The authors then demonstrated the applicability of this reaction system in a robust peptide and protein conjugation process with aniline derivatives.…”
Section: Selective Functionalization and Conjugation At Tyr Residues ...mentioning
confidence: 99%
“…Jiang et al recently disclosed the identication of a novel 1,3,5-triazine-pyridine (TPC) reagent (127) for Tyr-specic protein conjugation (Fig. 31).…”
Section: Tyr Bioconjugationmentioning
confidence: 99%